Przewlekły krwiak podtwardówkowy u chorej przyjętej do Kliniki Geriatrii z powodu postępującego otępienia - opis przypadku = Chronic subdural hematoma in patient admitted to Geriatric Department because of progressive dementia - case report - Emilia Główczewska-Siedlecka; Katarzyna Mądra-Gackowska; Krystyna Nowacka; Zygmunt Siedlecki; Mateusz Szostak; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2017)
Główczewska-Siedlecka Emilia, Mądra-Gackowska Katarzyna, Nowacka Krystyna, Siedlecki Zygmunt, Szostak Mateusz, Kędziora‑Kornatowska Kornelia. Przewlekły krwiak podtwardówkowy u chorej przyjętej do Kliniki Geriatrii z powodu postępującego otępienia - opis przypadku = Chronic subdural hematoma in patient admitted to Geriatric Department because of progressive dementia - case report. Journal of Education, Health and Sport. 2016;6(11):398-403. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168426 http://ojs.ukw.edu.pl/index.php/johs/article/view/4015       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 25.11.2016.       Przewlekły krwiak podtwardówkowy u chorej przyjętej do Kliniki Geriatrii z powodu postępującego otępienia - opis przypadku   Chronic subdural hematoma in patient admitted to Geriatric Department because of progressive dementia - case report   Główczewska-Siedlecka Emilia1, Mądra-Gackowska Katarzyna1, Nowacka Krystyna2, Siedlecki Zygmunt3, Szostak Mateusz3, Kędziora-Kornatowska Kornelia1   1. Katedra i Klinika Geriatrii, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 3. Klinika Neurochirurgii, Neurotraumatologii i Neurochiurgii Dziecięcej, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu         Streszczenie Przewlekłe krwiaki podtwardówkowe są schorzeniem typowym dla osób wieku podeszłym, objawiać się mogą zaburzeniem funkcji poznawczych, co u starszych chorych wymaga różnicowania z postępującym otępieniem. W niniejszej publikacji przedstawiony jest przypadek 85-letniej chorej przyjętej do Kliniki Geriatrii CM UMK w Bydgoszczy z powodu objawów postępującego otępienia. Badania psychologiczne wykazały istotne odchylenia w zakresie funkcji poznawczych. W badaniu TK głowy wykazano obecność rozległego przewlekłego krwiaka przymózgowego. Chora została poddana leczeniu operacyjnemu drogą trepanacji otworkowej. Przebieg okołooperacyjny był niepowikłany. Dwa tygodnie po zabiegu zaobserwowano poprawę w zakresie funkcji poznawczych. Opisany przypadek dowodzi znaczenia, jakie przewlekłe krwiaki podtwardówkowe odgrywają wśród chorych leczonych na oddziałach geriatrycznych.   Słowa kluczowe: przewlekły krwiak podtwardówkowy, otępienie, geriatria       Abstract Chronic subdural hematomas (CSDH) are typical for elderly people, its symptoms can be cognitive impairment, which in older patients require differentiation of the progressive dementia. In this publication, we presented a case of 85-year-old patient admitted to the Department of Geriatrics of CM UMK in Bydgoszcz with symptoms of progressive dementia. Psychological tests showed significant cognitive impairment. The CT scan revealed the presence of extensive CSH. The patient underwent surgical treatment through burrhole. Perioperatively no complitations happened. Two weeks later improvement in cognitive function was observed. This case improved the importance of CSDH in geriatrics.   Key words: CSDH, dementia, geriatrics